The challenge of Islamists for EU and US policies: Conflict, stability and reform - Muriel Asseburg; Daniel Brumberg (Stiftung Wissenschaft und Politik (SWP), 2007)
Islamist politics pose one of the most important and complex set of challenges that the US and Europe face today. Foreign policies have not reflected that complexity adequately, but have focused to a large degree on Islamist actors with a global jihadist agenda and the global "war on terror." Also, while the debates in the academic and think tank community around the inclusion of moderate Islamists have found their way into US democracy promotion approaches, they have been much less reflected in European policies. This volume therefore sheds light on some of the issues linked to political Islam.The contributions revolve around a set of overlapping questions: * What is the relevance of Islamist actors for the peaceful transition of authoritarian systems? * What can we learn from the inclusion of Islamists in Muslim majority democracies such as Turkey or Indonesia? * What is the relevance of Islamist actors for the peaceful transformation of conflicts in cases such as Sudan or Somalia? * What are EU and US approaches and policies towards Islamist actors and governments in the Muslim world? * What would a shared transatlantic agenda towards the Muslim world look like, and in which policy fields are cooperation, coordination, or a division of labor most promising?The volume is based on selected and edited contributions to a workshop that was co-organized by SWP, the German Institute for International and Security Affairs, and the United States Institute of Peace (USIP) on 27-28 September 2007. The workshop was part of the "Diverging Views on World Order? Transatlantic Foreign Policy Discourse in a Globalizing World" project that has been conducted by SWP with a whole range of US partner institutes since 2002 with the generous support of the German Marshall Fund (GMF)
Keywords: 320